Enhanced Efficiency and Stability in Sb2S3 Seed Layer Buffered Sb2Se3 Solar Cells. Issue 21 (12th May 2022) - Amin, Al; Li, Dian; Duan, Xiaomeng; Vijayaraghavan, S. N.; Menon, Harigovind G.; Wall, Jacob; Weaver, Mark; Cheng, Mark Ming‐Cheng; Zheng, Yufeng; Li, Lin; Yan, Feng
Abstract: Antimony selenide (Sb2 Se3 ) has excellent directional optical and electronic behaviors due to its quasi‐1D nanoribbons structure. The photovoltaic performance of Sb2 Se3 solar cells largely depends on the orientation of the nanoribbons. It is desired to grow these Sb2 Se3 ribbons normal to the substrate to enhance photoexcited carrier transport. Therefore, it is necessary to develop a strategy for the vertical growth of Sb2 Se3 nanoribbons to achieve high‐efficiency solar cells. Since antimony sulfide (Sb2 S3 ) and Sb2 Se3 are from the same space group (Pbnm) and have the same crystal structure, herein an ultrathin layer (≈20 nm) of Sb2 S3 has been used to assist the vertical growth of Sb2 Se3 nanoribbons to improve the overall efficiency of Sb2 Se3 solar cell. The Sb2 S3 thin layer deposited by the hydrothermal process helps the Sb2 Se3 ribbons grow normal to the substrate and increases the efficiency from 5.65% to 7.44% through the improvement of all solar cell parameters. This work is expected to open a new direction to tailor the Sb2 Se3 grain growth and further develop the Sb2 Se3 solar cell in the future. Abstract : A thin Sb2 S3 seed layer is utilized for the Sb2 Se3 thin film solar cells to regulate the (Sb4 Se6 ) n nanoribbons growth normal to the substrate. The Sb2 Se3 with Sb2 S3 seed layer achieves improved device performance through the improvement of all solar cell device parameters. This Sb2 S3 seed layer also improves the device stability.